Variation of pressure from cervical to distal end of oesophagus during swallowing: Study of a mathematical model - Pandey S.K.; Ranjan G.; Tiwari S.K.; Pandey K. (My University, 2025)
The investigation is an attempt to explore the cause that generates high pressure in the distal oesophagus compared to that in the proximal part. We observe through computer simulation that peristaltic waves of even slightly but progressively increasing amplitude can generate high pressure near the distal end. This is illustrated through exponential growth in the wave amplitude, which represents the dependence of the rate of growth of amplitude on its current magnitude. This may be physically interpreted that the generation of high pressure in the lower oesophagus ensures complete bolus delivery to the stomach through the cardiac sphincter. This finding may prove to be a very prominent result towards creating a prosthetic oesophagus. Some more conclusions with regard to progressive exponential increase in amplitude are also drawn. The pressure falls to zero invariably in the proximal half of every bolus, whereas for constant amplitude, zero pressure is located exactly at the midpoints of the boluses for Newtonian flows. Backward flow of fluid takes place in a smaller region if amplitude increases. Circular muscles contract more in the lower oesophagus to generate higher pressure in the distal oesophagus. In a sharp contrast to the case of constant-amplitude, pressure is neither uniformly distributed in a wave, nor is of identical shape for all boluses in the case of train wave propagation. Pressure distribution along the axis of the oesophagus differs in shape and magnitude both when a single wave propagates. © 2017 Elsevier Inc.